Pengaruh Likuiditas, Solvabilitas, Profitabilitas, Pasar terhadap Harga Saham pada Perusahaan Otomotif yang tedaftar di Bursa Efek Indonesia - Sandro Heru Yusuf Arifandi; Siti Masyithoh; Anisa Kusumawardani (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Sandro Heru Yusuf Arisandi. 2019. The Influence of Liquidity, Solvability, Profitability, Market on Share Price in Automotive Company Registered on Indonesia Stock Exchange. Under the guidance of Siti Masyithoh and Anisa Kusumawardhani. This research aimed to know and to analyse how big the influence of ratio of liquidity, solvability, profitability, market on share price in automotive company registered on Indonesia Stock Exchange in 2013-2017. This research used secondary data obtained from the website of Indonesia Stock Exchange (IDX) with purposive sampling data collection method. In this research, there were samples taken from 9 automotive company in 2013-2017. Data collection was done using literature and empirical study. Data analysis technique used was multiple linear regression. The result of this research using F test showed that the variable of current ratio (X1), debt to equity ratio (X2), return on assets (X3)and price earning ratio (X4) (together) significantly influenced to share price of automotive company registered on Indonesia Stock Exchange (IDX) in 2013-2017. T test result showed that the variable of current ratio (X1), debt to equity ratio (X2), return on assets (X3) and price earning ratio (X4 ) has significant positive effect on share price of automotive company registered on Indonesia Stock Exchange (IDX) in 2013-2017.